2012
DOI: 10.1186/1743-8977-9-40
|View full text |Cite
|
Sign up to set email alerts
|

Effect of co-exposure to nickel and particulate matter on insulin resistance and mitochondrial dysfunction in a mouse model

Abstract: BackgroundIt has been well recognized that toxicity of fine ambient air particulate matter (PM2.5) may depend on its chemical constituents, including components such as soluble metals that may theoretically exert distinctive effects. We have recently demonstrated an important effect of PM2.5 on metabolic function. Since transition metals, such as nickel (Ni), represent an important component of exposure in certain environments, and may significantly influence the toxicity of inhalational exposure, we investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 34 publications
3
43
0
Order By: Relevance
“…This approach was used by Xu et al (2012) in which mice were exposed to nickel sulfate, CAPs, or a combination of nickel sulfate and CAPs; they showed that nickel and CAPs had synergistic effects on some of the metabolic and inflammatory endpoints measured; Huang et al (2012) observed synergistic effects of NO 2 and fine CAPs on cardiovascular responses in healthy young volunteers.…”
Section: Common Issues and Considerationsmentioning
confidence: 99%
“…This approach was used by Xu et al (2012) in which mice were exposed to nickel sulfate, CAPs, or a combination of nickel sulfate and CAPs; they showed that nickel and CAPs had synergistic effects on some of the metabolic and inflammatory endpoints measured; Huang et al (2012) observed synergistic effects of NO 2 and fine CAPs on cardiovascular responses in healthy young volunteers.…”
Section: Common Issues and Considerationsmentioning
confidence: 99%
“…Niu et al (2013) noted that metallic components of PM may be responsible for the cardiovascular disorders produced by PM exposures. Nickel has long been reported from epidemiological and molecular studies to promote cardiovascular disease (Bell et al, 2014; Ying et al, 2013), respiratory cancers (Grimsrud and Peto, 2006), insulin resistance (Xu et al, 2012) and mortality (Laden et al, 2000). Hsu and Lippmann (2007) previously found that the levels of Ni in concentrated ambient particulate (CAP) matter PM 2.5 were strongly correlated to acute changes in heart rates and their variability.…”
Section: Discussionmentioning
confidence: 99%
“…Mass-spectrometry analysis has already demonstrated the presence of aldehydes, free radicals, and metals which are known mitochondrial toxicants and may act through similar disease mechanisms as those triggered by cigarette smoke exposure 312317 . Other tobacco products including hookahs, little cigars, and cigarillos combust tobacco leaves in a fashion very similar to traditional cigarettes and therefore, likely contain the same toxicants and carcinogens found in tobacco cigarette smoke.…”
Section: Future Directionsmentioning
confidence: 99%